Analisis penggunaan deiksis dalam novel -8 °C (Kutemukan Dirimu Dalam Mimpiku) karya Angga Fauzan - Nadya, Alissa Qotrun (Maliki Interdisciplinary Journal, 2024)
This study aims to identify and describe the types and functions of deixis in the novel -8 °C (Kutemukan Dirimu Dalam Mimpiku) by Angga Fauzan. This study uses a qualitative approach using descriptive methods. The source of the data in this study is the novel -8 °C -8 °C (Kutemukan Dirimu Dalam Mimpiku) by Angga Fauzan. In this study, the researcher uses four types of deixis in the novel-8°C -8 °C (Kutemukan Dirimu Dalam Mimpiku) by Angga Fauzan, namely (1) persona deixis, (2) place deixis, (3) time deixis, (4) discourse deixis. The deictic functions found are (1) the function of persona deixis includes the function of referring to the person who is speaking, the person being spoken to, and the person being spoken to, (2) the deixis function of place includes the function of referring to places that are close to the speaker and far from the speaker, (3 ) the function of time deixis includes the function of referring to before the speech, during the speech, and after the speech, and (4) the function of discourse deixis includes the function of referring to things that have been mentioned and things that will be mentioned.